Activated hepatic stellate cells promote epithelial-to-mesenchymal transition in hepatocellular carcinoma through transglutaminase 2-induced pseudohypoxia. (December 2018) - Ma, Hui; Xie, Liqi; Zhang, Lan; Yin, Xin; Jiang, Hucong; Xie, Xiaoying; Chen, Rongxin; Lu, Haojie; Ren, Zhenggang
Abstract Activation of hepatic stellate cells reportedly contributes to progression of hepatocellular carcinoma (HCC). Herein, we use quantitative proteomics and ingenuity pathway analysis to show that transglutaminase 2 (TGM2) is upregulated in the course of activated hepatic stellate cells promoting epithelial-mesenchymal transition (EMT) in HCC-derived cells both in vivo and in vitro. Mechanistically, activated hepatic stellate cells promote TGM2 upregulation in HCC cells through inflammatory signalling; and TGM2-induced depletion of von Hippel-Lindau (VHL) protein, a key molecule in the degradation of hypoxia inducible factor-1a (HIF-1a) under normoxia, then causes HIF-1a to accumulate, thereby producing a pseudohypoxic state that promotes EMT in HCC cells. These findings suggest that the promotion of EMT in HCC cells by activated hepatic stellate cells is mediated by pseudohypoxia induced via TGM2/VHL/HIF-1a pathway. Hui Ma et al. report a new mechanism by which activated hepatic stellate cells promote the epithelial-to-mesenchymal transition (EMT) in hepatocellular carcinoma. They find that transglutaminase 2 is upregulated by activated hepatic stellate cells via inflammatory signalling, which leads to a pseudohypoxic state promoting EMT.